Global Society, Cosmopolitanism and Human Rights. - Cotesta, Vittorio (Cambridge Scholars Publishing, 2013)
Global Society, Cosmopolitanism and Human Rights is the outcome of a decade-long scholarly project. The point of convergence emerging from the analyses contained in this volume is that ""global society"", ""cosmopolitanism"" and ""human rights"" are likely to constitute the basis of present and future ways of life. The ""project for humanity"" of the future, while resting on local social associations, will have ""globality"" as its reference. A world dominated by globalisation processes obliges the so ...